2012
DOI: 10.1029/2011ja017033
|View full text |Cite
|
Sign up to set email alerts
|

A study of the changes of the near‐Earth plasma sheet and lobe driven by multiple substorms: Comparison with a full particle simulation of reconnection

Abstract: [1] Comparisons of multispacecraft observations and full-particle simulations are used to understand magnetotail changes during substorms and the related cross-tail current disruptions/reductions. We first show that the electric field accompanying current disruptions can be measured in the tail lobe from the drift velocity of oxygen beams. A stormy period is studied here with a fleet of spacecraft including the four Cluster spacecraft and the Double Star spacecraft TC-1 in the tail, ACE and Geotail respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It is likely that such smaller scale dipolarizations (compared to substorm onset events) also give rise to enhanced E-fields in the tail lobe, such as observed by Sauvaud et al (2012) at substorm onsets. The role of Earthward-propagating dipolarisation front flow bursts within X = −20 to −10 R E as a basic element (substructure) in the substorm process in the magnetotail is emphasized by Lyons et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that such smaller scale dipolarizations (compared to substorm onset events) also give rise to enhanced E-fields in the tail lobe, such as observed by Sauvaud et al (2012) at substorm onsets. The role of Earthward-propagating dipolarisation front flow bursts within X = −20 to −10 R E as a basic element (substructure) in the substorm process in the magnetotail is emphasized by Lyons et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous observations of the Double Star, Cluster, Geotail and five geostationary LANL satellites revealed according to Sauvaud et al (2012) that the dynamics of changes in the plasma sheet and of the geomagnetic field in the magnetospheric tail repeats every 2-4 h. The analysis of these results allowed determining the approximate location in the tail where the dipolarisations are initiated and the propagation direction of the disturbances. Each substorm complies with an energy-loading period, which is then followed by a dipolarisation at geocentric distances between 11 and 18 R E .…”
Section: Behaviour Of the Discrete Auroral Formsmentioning
confidence: 99%
“…They precede the plasma particle injections at the geostationary orbit of 6.6 R E . Sauvaud et al (2012) showed that the onset of the magnetic energy conversion occurs at a tailward distance of 10-11 R E and propagates then both toward the Earth and toward the distant magnetospheric tail. According to Pudovkin et al (1991), the creation phase is dominated by an enhancement of the dawn-dusk electric field, magnetic field stretching, and plasma sheet thinning.…”
Section: Behaviour Of the Discrete Auroral Formsmentioning
confidence: 99%
“…During transport into the lobes, electric field modulations may also affect the O + trajectories. Such modulations may consist of Alfvèn waves propagating in the lobes , convection pulses propagating at low velocity in the lobes and possibly triggered by IMF B z turnings (Maggiolo et al 2006) or by dipolarization fronts associated with substorms (Sauvaud et al 2012).…”
Section: Convection and Velocity Filter Effectmentioning
confidence: 99%